Aumolertinib Effectively Reduces Clinical Symptoms of an EGFR L858R-Mutant Non-Small Cell Lung Cancer Case Coupled With Osimertinib-Induced Cardiotoxicity: Case Report and Review - Zhang, Qianqian; Liu, Haiyang; Yang, Jia (Frontiers in Endocrinology, 2022)
Osimertinib, a third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) first-line therapy, has shown good clinical outcomes in non-small cell lung cancer (NSCLC), but some serious adverse events such as cardiotoxicity have also been reported. Here, we present the first NSCLC case with osimertinib-induced cardiac failure. The case is successfully being treated by switching to another third-generation TKI, aumolertinib. A 62-year-old non-smoking woman was initially diagnosed with stage cT2aN2M1c IVB NSCLC with synchronous brain and bone metastasis in April 2020. Further genetic screening of the patient identified Leu858Arg (L858R) mutation in EGFR; thus, the patient was administered third-generation TKI osimertinib (80 mg/day) for 6 months. This treatment with osimertinib led to serious cardiac failure but no significant reduction in NSCLC tumor size. To cope with these conditions, another third-generation TKI, aumolertinib (110 mg/day), along with a supplement treatment plan was prescribed to the patient. Interestingly, this new treatment plan of aumolertinib significantly inhibited tumor growth in 8 months. Therefore, we conclude that the administration of second-line aumolertinib 110 mg/day has fewer adverse reactions and high efficacy against NSCLC as compared to osimertinib therapy.